Kazantzakis’s Odyssey as a Value and its Place in Education - Κουμάκης, Γιώργος; Οικονόμου, Αναστασία (Education Sciences, 2019)
This paper attempts to highlight the difficulties of understanding Nikos Kazantzakis’s Odyssey and his poetry in general. The foundation of the Odyssey and his work as a whole is philosophical, the author having received an education in philosophy from Bergson in Paris. I attempt to interpret certain obscure but profound poetic excerpts, such as that asserting that death makes life tastier. Another excerpt interpreted here is that the soul bends more before joy than before pain and sorrow. The analyses show that the Odyssey is valuable due to its wonderful plot, its diction and the excellent messages that it broadcasts to humanity as a whole and the younger generations in particular.